2019
DOI: 10.1177/0142723719834102
|View full text |Cite
|
Sign up to set email alerts
|

Deaf children need language, not (just) speech

Abstract: Deaf and Hard of Hearing (DHH) children need to master at least one language (spoken or signed) to reach their full potential. Providing access to a natural sign language supports this goal. Despite evidence that natural sign languages are beneficial to DHH children, many researchers and practitioners advise families to focus exclusively on spoken language. We critique the Pediatrics article ‘Early Sign Language Exposure and Cochlear Implants’ (Geers et al., 2017) as an example of research that makes unsupport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 125 publications
(175 reference statements)
4
124
0
9
Order By: Relevance
“…The researchers concluded that their study offered "the most compelling support yet available in CI literature for the benefits of spoken language input for promoting verbal development in children implanted by 3 years of age" (p. 1). However, as Hall et al [33] explain, the study presents no evidence that there is a causal relationship between the use of signing and lower achievement, and it is quite possible that Geers et al's results "reflect a self-selection effect, where children who fare best in spoken language gravitate to oral-only environments while children who struggle in spoken language remain in or seek out sign language and manual communication environments" [33] (p. 6).…”
Section: The Bilingual Paradoxmentioning
confidence: 79%
See 4 more Smart Citations
“…The researchers concluded that their study offered "the most compelling support yet available in CI literature for the benefits of spoken language input for promoting verbal development in children implanted by 3 years of age" (p. 1). However, as Hall et al [33] explain, the study presents no evidence that there is a causal relationship between the use of signing and lower achievement, and it is quite possible that Geers et al's results "reflect a self-selection effect, where children who fare best in spoken language gravitate to oral-only environments while children who struggle in spoken language remain in or seek out sign language and manual communication environments" [33] (p. 6).…”
Section: The Bilingual Paradoxmentioning
confidence: 79%
“…This has led to cochlear implantation becoming the standard of care for deaf children in developed countries. In many cases, parents are discouraged from signing with their deaf children based a limited set of studies that suggest that the acquisition of sign language may interfere with speech development (see [33,34]). Even where parents are not explicitly discouraged from signing, the success of cochlear implants-coupled with the difficulties associated with acquiring a new language-mean that the vast majority of hearing parents are not choosing to sign with their deaf children [3].…”
Section: Deaf Children Whose Home Language Is Spoken Englishmentioning
confidence: 99%
See 3 more Smart Citations